(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The article analyzes the legislative measures enacted during the emergency situation from the standpoint of the sources of law and of their impact on already discriminated or vulnerable people. The study focuses on the impact of these measures on women, people with disabilities, migrants and detainees. The described situation has therefore challenged the principles of constitutionalism.